KARAKTERISTIK MORFOMETRI DAN MORFOTEKTONIK DAS CIBEET SEGMEN SELAAWI GIRIJAYA DAN DAS CIKUNDUL SEGMEN CIBADAK MAJALAYA, KABUPATEN CIANJUR, PROVINSI JAWA BARAT - Anfasha, Arifin; Pranantya, Pulung Arya; Sukiyah, Emi (Bulletin of Scientific Contribution, 2016)
West Java is an area that has a high vulnerability to disasters, the condition is influenced by a complex geological structure so prone to geological disasters, and faults can be studied by morphotectonic study approach. With morphometric analysis were used to identify the character of the shape of a region and its relation to the level of tectonic activity. Comparison of morphotectonic aspects of the Quaternary and Tertiary age rocks will involve active tectonic processes in it. Research carried out by three methods, namely studio methods with data measuring of straightness of the ridge and valleys, Rb, Dd, and Smf, field methods by means of geological mapping data retrieval strike / dip, fractures, megascopic descriptions of rock, image capture of the field, laboratory methods by analyzing fracture data and verification of field data with the data link between the studio and the activeness of faults in the study area. The activeness of fault and other geomorphological parameters can be determined by a variety of morphotectonic approaches, morphotectonic parameters such as Rb, Dd, Smf and straightness of ridge and valleys has become a reference in determining the activeness. The geological structure in the area of research are in form of faults and  fractures, which relatively trending northwest - southeast. Fault is evidenced by their straightness of DEM image as well as fracture data  found in the field.   Keyword : Morphometry, Morphotectonic, Watershed, Active tectonic, DEM Jawa Barat merupakan salah satu wilayah yang memiliki kerawanan bencana tinggi, kondisi ini dipengaruhi oleh tatanan geologi yang kompleks sehingga rawan dengan bencana geologi, sesar dapat diketahui dengan pendekatan studi morfotektonik. Dengan cara analisis morfometri digunakan untuk mengidentifikasi karakter bentuk suatu wilayah dan kaitannya dengan tingkat aktivitas tektonik. Perbandingan aspek-aspek morfotektonik pada batuan berumur Kuarter dan Tersier akan melibatkan proses tektonik aktif di dalamnya. Penelitian dilakukan dengan  tiga metode yaitu metode studio dengan pengukuran data kelurusan punggungan, lembahan, Rb, Dd dan Smf, metode lapangan dengan cara pemetaan geologi pengambilan data strike/dip,kekar,deskripsi batuan secara megaskopis, pengambilan foto lapangan, metode laboratorium dengan menganalisi data kekar dan mengintervetasi pembuktian data lapangan dengan data studio dan adanya keterkaitan antara keaktifan sesar di wilayah penelitian. Keaktifan sesar dan parameter geomorfologi dapat diketahui dengan berbagai pendekatan morfotektonik, Parameter morfotektonik seperti Rb, Dd, Smf dan Kelurusan tersebut menjadi acuan dalam menentukan keaktifan. Struktur geologi di daerah penelitian berupa kekar dan sesar yang berarah relatif barat laut – tenggara. Sesar tersebut dibuktikan oleh adanya kelurusan dari citra DEM serta data kekar yang ditemukan dilapangan.Kata kunci : Morfometri, Morfotektonik, DAS, Tektonik aktif, DEM